Linearization of an optically sampled analog-to-digital converter - Wong, Jia Haur (2013)
In this paper, we show experimentally for the first time a 2 GSamples/s optically sampled analog-to-digital converter based on dual-output modulation and balanced photodetection scheme. Linearization in the form of arcsine operation is also described to illustrate the considerations of the proposed scheme. Finally, arcsine operation is digitally implemented on the output of the electronic ADC and is shown to enable significant odd-order harmonic suppression at high modulation depths approaching unity.